Comparison of different electrotherapy methods and exercise therapy in shoulder impingement syndrome: A prospective randomized controlled trial - Sevtap Gunay Ucurum; Derya Ozer Kaya; Yasemin Kayali; Ayhan Askin; Mustafa Agah Tekindal (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to assess and compare the effects of different electrotherapy methods and exercise therapy on pain, function and quality of life in shoulder impingement syndrome. Methods: Eighty-three patients (66 females, 17 males; mean age: 48.2 ± 7.33 years) with shoulder impingement syndrome were selected and 79 of them were randomly allocated into four groups. Group 1 (n = 19, mean age: 47.89 ± 7.12 years) was given hot pack and exercises, Group 2 (n = 20, mean age: 47.70 ± 6.51 years) was given hot packs, exercises and interferential current, Group 3 (n = 20, mean age: 48.50 ± 8.34 years) was given hot packs, exercises and TENS and Group 4 (n = 20, mean age: 48.55 ± 7.89 years) was given hot packs, exercises and ultrasound three times a week for four weeks. Assessments were made before treatment, right after it and three months after that using the visual analog scale (VAS), Short Form-36 (SF-36) and the Disabilities of the Arm, Shoulder and Hand (DASH) outcome measures. Results: At the fourth week and third month assessments, all groups showed significant improvements in terms of pain, DASH and SF-36 physical component scores (p < 0.05). In intragroup comparisons, a significant difference between pre- and post-treatment results was found only in SF-36 mental component scores of Group 2. No significant difference was observed between the groups in any stage of the study period (p > 0.05). Conclusion: Application of ultrasound, interferential current and TENS in addition to exercise therapy in shoulder impingement syndrome treatment had similar improvements in terms of pain, function and physical component of quality of life. However, interferential current treatment showed significantly better outcomes for the mental component of quality of life. Level of evidence: Level I, Therapeutic study. Keywords: Electrotherapy, Exercises, Pain, Quality of life, Shoulder impingement syndrome